Development of Online Media to Deliver Guidance and Counseling Services in during the Covid-19 Pandemic - Waroka, Linda Ardiya (Universitas Mercu Buana Yogyakarta, 2022)
The condition of school from home provides a challenge for Guidance and Counseling teachers. Students begin to feel bored to talk to in monotonous, rigid conditions. Guidance and counseling innovation is intended as the ability to apply creative solutions to various problems and opportunities to improve the performance of GC services, so the purpose of this research is to find out the development of GC teacher services ( counseling guidance) in the Merdeka Learning era during the covid-19 pandemic. This study uses a qualitative research type. The data analysis used in ringing this article is library research. The results of the research on the development of GC teacher services are the use of online media such as zoom, gmeet, gform, hatsapp, google classroom, peer counselors, development of GC teacher abilities, development oftutorials self-healing and development of gadget constraints and student quotas